Value of Exfoliative Cytology in the Early Detection of Breast Carcinoma - Coutinho, Alberto (2023)
The authors report the diagnosis of 3 cases of non infiltrant duct carcinoma of the breast through cytological examination of the mamary discharge in 1,450 patients of the National Institute of Cancer (Rio de Janeiro, GB — Brazil); the 3 patients in whom the presence of malignant cells in mammary discharge was demonstrated had neither palpable tumor nor any other sign or symptom apart from the mammary discharge; they are alive and well after surgery performed 14, 10 and 5 years ago, respectively. Those are the possibilities of exfoliative cytology in the detection and early diagnosis of breast carcinoma.